Minimum Wage Effects on Human Capital Accumulation: Evidence from Canadian Data - Diana Alessandrini; Joniada Milla (Institute of Labor Economics (IZA), 2021)
This paper investigates the impact of the minimum wage on individuals' schooling decisions and the type of human capital acquired by students. Using Canadian longitudinal data, we explore 136 minimum wage amendments across provincial jurisdictions, and find three novel results. First, the minimum wage affects both the quantity and the type of human capital acquired by individuals. High minimum wages stimulate the accumulation of occupation-specific human capital at community colleges but discourage enrollment in academic programs offered by universities. Quantitatively, a 10% increase in the minimum wage increases community-college enrollment by 6% and reduces university enrollment by 5%. Second, high minimum wages strengthen the link between parental background and children educational attainment, worsening the university participation gap between individuals with high and low parental education. Finally, minimum wages also affect whether students dropout of post-secondary education or return to school later in life as mature students.
Keywords: J31; J38; J24; I23; 330; minimum wage; post-secondary enrollment; post-secondary dropouts